2002
DOI: 10.1007/s12012-002-0006-3
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid metabolites act to increase contractility in isolated rat heart

Abstract: Previous in vivo studies in dogs suggest that the 9,10-monoepoxide of linoleic acid (9,10-cis-epoxyoctadecenoic acid [9,10-EOA]) has toxic cardiovascular effects that result in death at higher doses. More recent work with rabbit renal proximal tubule cells suggests that the 12,13-metabolites of linoleic acid are more toxic than the 9,10-isomers. Thus, in the current study, we tested the hypothesis that 12,13-EOA and 12,13-dihydroxyoctadecadienoic acid (12,13-DHOA) have direct adverse effects on the heart. Lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The main caveat of these studies, which reported that EpOMEs and DiHOMEs have toxic effects, is that very high concentrations (100–500 μM) were used [48]. Contrary to these reports, lower, more physiological concentrations of EpOMEs and DiHOMEs did not have toxic effects and rather had beneficial effects [61]. Mitchell et al reported that LA and its oxidative metabolites (EpOMEs and DiHOMEs) did not have toxic effects during acute exposure in Langendorff-perfused rat hearts [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main caveat of these studies, which reported that EpOMEs and DiHOMEs have toxic effects, is that very high concentrations (100–500 μM) were used [48]. Contrary to these reports, lower, more physiological concentrations of EpOMEs and DiHOMEs did not have toxic effects and rather had beneficial effects [61]. Mitchell et al reported that LA and its oxidative metabolites (EpOMEs and DiHOMEs) did not have toxic effects during acute exposure in Langendorff-perfused rat hearts [61].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these reports, lower, more physiological concentrations of EpOMEs and DiHOMEs did not have toxic effects and rather had beneficial effects [61]. Mitchell et al reported that LA and its oxidative metabolites (EpOMEs and DiHOMEs) did not have toxic effects during acute exposure in Langendorff-perfused rat hearts [61]. Pretreatment with 12,13-EpOME protected primary cultures of rabbit renal proximal tubular cells against hypoxia/reoxygenation injury [62].…”
Section: Discussionmentioning
confidence: 99%
“…However, the only lipids that were further increased in Tie2‐CYP2C8 Tr hearts compared to WT were 9,10‐ and 12,13‐DiHOME. At high levels (>10 μM), the EpOMEs or DiHOMEs have been reported to have a variety of effects, including cytotoxicity to renal tubules (31), stimulation of ROS production (32), increased contractility in rat hearts (52), cardiodepression in dogs (34), inhibition of papillary muscle contraction, and vasoconstriction of isolated arteries (33). To examine the role of DiHOMEs on functional outcomes after I/R, we treated WT hearts with physiologically relevant concentrations (250 nM) of 9,10‐DiHOME.…”
Section: Discussionmentioning
confidence: 99%
“…Their significance is unclear. The literature on LA oxylipins is limited and inconsistent; some, but not all, preclinical studies suggest these oxylipins are cardiotoxic [ 33 ]. Analysis of the EpOME/DiHOME and EpETE/DiHETE ratio for any NSAID use versus no NSAID use in all subjects or sex-stratified analyses were null (data not shown).…”
Section: Discussionmentioning
confidence: 99%